Climate changes of the northeastern Tibetan Plateau since the late glaciation inferred from clay mineralogy of sediments in Kuhai Lake. (8th June 2017) - Sun, Qingfeng; Colin, Christophe; Liu, Zhifei; Mischke, Steffen; Duchamp-Alphonse, Stéphanie; Zhang, Chengjun; Chen, Fahu
Abstract: A high-resolution study of clay mineralogy has been carried out on a sediment core recovered from Kuhai Lake in order to investigate climatic and environmental changes in the northeastern Tibetan Plateau since the late glacial period. Clay mineralogy reveals significant changes in sedimentary sources and hydrolysis conditions in the Kuhai Lake catchment area. Before 14.9 cal ka BP, the predominance of illite and relatively high amount of kaolinite, derived mainly from the reworking of sedimentary rocks, imply unstable cold-arid conditions and significant glacier cover that prevented from weathering of metamorphic and mafic rocks in the high relief of the catchment. Between 14.9 and 5.4 cal ka BP, an increase in smectite and chlorite contents associated with relatively low values of the illite chemistry index indicate that clay minerals derived from the weathering of metamorphic and volcanic rocks in the highlands of the catchment area. Such modifications were triggered by a melting of glaciers in the lake's catchment during the Bølling-Allerød interstadial, followed by an intensification of monsoon precipitations in the early Holocene (around 10.0 cal ka BP). Both processes are responsible for significant physical erosion in the highlands together with an efficient transport of smectite and chlorite from areas of high relief to the lake. After 5.4 cal ka BP, lower smectite and chlorite proportions, associated with a predominance of Al-rich illite and kaolinite, indicate a return to relatively dry conditions and a lowering of physical erosion in the drainage basin. Comparison between clay mineralogy and pollen records indicates that variations in weathering intensity in the Kuhai Lake catchment area and changes in its surrounding vegetation are synchronous, demonstrating the large potential of clay mineralogical analysis to trace climate change of the Tibetan Plateau.